2018
DOI: 10.1136/practneurol-2017-001835
|View full text |Cite
|
Sign up to set email alerts
|

You’ve made the diagnosis of functional neurological disorder: now what?

Abstract: Patients with functional neurological disorders (FND)/conversion disorder commonly present to outpatient clinics. FND is now a 'rule in' diagnosis based on neurological examination findings and semiological features. While neurologists may be more comfortable diagnosing patients with FND, there is only limited guidance as to how to conduct follow-up outpatient visits. Using clinical vignettes, we provide practical suggestions that may help guide clinical encounters including how to: (1) explore illness beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…[33][34][35] While the above components are core aspects of treatment, the identification of patient-specific predisposing vulnerabilities, acute precipitants, and perpetuating factors should be elucidated to help individualize treatments with these factors in mind. 36 In this case, predisposing vulnerabilities included early-life separation anxiety, dyslexia with academic difficulties, bullying at school, tendency to not verbalize stress and affective symptoms to supports, and the concurrent presence of another functional somatic disorder (irritable bowel syndrome). In the presented case, dystonia and pain symptoms occurred abruptly and spontaneously, though in the literature a minor physical injury has sometimes been described as precipitating onset of some FND presentations.…”
Section: Questions To the Consultantsmentioning
confidence: 92%
“…[33][34][35] While the above components are core aspects of treatment, the identification of patient-specific predisposing vulnerabilities, acute precipitants, and perpetuating factors should be elucidated to help individualize treatments with these factors in mind. 36 In this case, predisposing vulnerabilities included early-life separation anxiety, dyslexia with academic difficulties, bullying at school, tendency to not verbalize stress and affective symptoms to supports, and the concurrent presence of another functional somatic disorder (irritable bowel syndrome). In the presented case, dystonia and pain symptoms occurred abruptly and spontaneously, though in the literature a minor physical injury has sometimes been described as precipitating onset of some FND presentations.…”
Section: Questions To the Consultantsmentioning
confidence: 92%
“…Two of us (JC, TN) run specialist clinics for functional neurological disorders and one of us (KH) is the chief executive officer of a related charity (FND Action). We agree that a diagnosis of functional neurological disorder is sometimes made but not explained in a way that optimises patient understanding and acceptance of a complex disorder 2…”
mentioning
confidence: 88%
“…Lastly, we discuss the physician’s role in longitudinal follow-up. 27 , 28 While recent publications have suggested that specialized FND clinics should be integrated within neurology departments to aid patient care (a sentiment we support), 29 high prevalence rates suggest that both specialized tertiary care centers and community-based care will be needed to meet the needs of this prevalent patient population. As such, clinicians across the clinical neurosciences should develop proficiency in the outpatient assessment and management of mFND.…”
Section: Introductionmentioning
confidence: 93%
“… 42 , 75 Pictorial illustrations demonstrating useful approaches to the delivery of the diagnosis and follow-up discussions have been published and are helpful educational resources. 28 , 42 …”
Section: Delivering the Diagnosis And Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation